Analyse von Lösungswegen und Erweiterungsmöglichkeiten eines Problems für die Klassen 7–11 - Ambrus, Gabriella (Teaching Mathematics and Computer Science, 2007)
Making several solutions for a problem i.e. the generalization, or the extension of a problem is common in the Hungarian mathematics education. But the analysis of a problem is unusual where the connection between the mathematical content of the task and of its different formulations is examined, solutions from different fields of mathematics are presented regarding the knowledge of different age groups, the problem is generalized in different directions, and several tools (traditional and electronic) for solutions and generalizations are presented. This kind of problem analysis makes it viable that during the solution/elaboration several kinds of mathematical knowledge and activities are recalled and connected, facilitating their use inside and outside of mathematics. However, an analysis like this is not unfamiliar to the traditions of the Hungarian problem solving education – because it also aims at elaborating a problem – but from several points of view. In this study, a geometric task is analysed in such a way.